THE INSTITUTIONALIZATION OF SEXUAL KNOWLEDGE IN BRAZIL: SEXOLOGY AND SEXUAL EDUCATION FROM THE XIX CENTURY TO OUR DAYS - Bedin, Regina Celia [UNESP]; Muzzeti, Luci Regina [UNESP]; Marcal Ribeiro, Paulo Rennes [UNESP] (Fundacao Univ Tocantins, 2020)
The article analyzes the construction of sexual knowledge in Brazil since the 19th century, starting from medical schools and the production of thesis; going through the first decades of the 20th century and the production of sexology and sex education books; until the 1960s, with the identification of the first schools to have sex education. Then, it analyzes the dictatorial period that the country went through, from 1964 to 1985, when medical scientific societies made studies and discussions about sex and sexuality. After the end of the dictatorship, sexual knowledge was consolidated in universities. Research groups emerged, giving new impetus to sex education, making Brazil an important pole of theoretical discussion and proposals for intervention in this field of knowledge. It ends with an analysis of the current moment, in which conservative thinking of right wing takes hold of Brazilian society and stimulates discourses and actions that are contrary to sex education and all reflections, criticisms and interventions related to gender, sexuality and freedom expression.
Keywords: Sexual education; Sexual knowledge; History of sexual education; Institucionalization of sexual knowledge; Brazil